Pengaruh Social Comparison dan Perfectionism terhadap Body Image pada Beauty Content Creator di Komunitas Kecantikan @beautychannel.id - Djaelani, Bella Prameswari Putri; Akbar, Rifqi Farisan (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Social media has changed the way individuals view their body image, especially for beauty content creators who are influencers who play a role in forming online beauty and lifestyle communities that are often exposed to ideal beauty standards. This study aims to measure the effect of social comparison and perfectionism on body image in beauty content creators in the @beautychannel.id beauty community. This study involved 121 respondents who were taken using a simple random sampling technique which was then analyzed using multiple linear regression. The results showed that social comparison and perfectionism together had an effect of 30.6% on body image, with social comparison having an impact of 25.5% and perfectionism of 9.9%. The results of this study indicate that the higher the social comparison and perfectionism possessed by beauty content creators, the higher the dissatisfaction with body image.